Political economy of Agrarian Conflict of Small Island: Case Study in Pari Island, Seribu Islands, Capital Province of Jakarta - Christian, Yoppie; Satria, Arif; Sunito, Satyawan (Sodality: Jurnal Sosiologi Pedesaan, 2018)
ABSTRACTA small island of Pari currently experiencing agrarian conflicts over land involving locals and tourism corporations. This conflict has lasted for more than twenty years and there has been no solution to this dispute. This research chooses a case study approach to discover how the appropriation of the means of production by capital to Pari’s locals and analyze the critical point of capital penetration into the insular region. The data were taken using observation, interviews, archives, focused discussions, and mass-media as a qualitative analysis material by generalizing the empirical findings into the intermediate theoretical analysis. The results show that this process of dispossession involves the state apparatus essentially by manipulating the lack of local knowledge of the formal property system and the application of pseudo-legal system to strengthen the land acquisition process. The Marxian political economic perspective sees the relation between corporation and state in land dispossession in Pari is in order to create a pre-condition for the formation of a new space of capitalism. This new space is based on primitive accumulation by separating humans from their means of production and creating landless people as the foundation for the operation of capital accumulation by the tourism industry and potentially excluding fishers or local communities as actors in small island resource management.Keywords: accumulation by dispossesion, agrarian conflict, political economy, small islandABSTRAKPulau kecil Pari saat ini mengalami konflik agraria atas tanah yang melibatkan masyarakat lokal dan korporasi wisata. Konflik ini telah berlangsung selama lebih dari duapuluh tahun dan belum ada solusi atas sengketa ini. Penelitian ini memilih pendekatan studi kasus untuk menemukan cara kerja perampasan alat produksi oleh kapital terhadap wargan Pari dan menganalisis kegentingan dari penetrasi kapital ke wilayah insular. Data diambil memanfaatkan observasi, wawancara, arsip, diskusi terfokus, dan media massa sebagai bahan analisis secara kualitatif dengan menggeneralisasi temuan empirik dalam analisis teoritik level menengah. Hasil penelitian menunjukkan bahwa proses perampasan ini melibatkan aparat negara secara esensial dengan cara memanipulasi ketiadaan pengetahuan warga lokal terhadap sistem properti formal dan bekerjanya sistem pseudo-legal untuk menguatkan proses akuisisi tanah tersebut. Perspektif ekonomi politik Marxian dalam penelitian ini melihat bahwa relasi kapitalistik antara korporasi dan negara dalam perampasan tanah di Pari adalah dalam rangka menciptakan pra-kondisi bagi pembentukan ruang baru kapitalisme. Ruang baru ini berbasis akumulasi primitif dengan melucuti manusia dari alat produksi dan menciptakan manusia tanpa tanah sebagai fondasi bagi operasi akumulasi kapital oleh industri wisata dan berpotensi menyingkirkan nelayan atau masyarakat lokal sebagai aktor dalam pengelolaan sumber daya pulau kecil.Kata kunci: akumulasi dengan perampasan, ekonomi politik, konflik agraria, pulau kecil